ATF6 decreases myocardial ischemia/reperfusion damage and links ER stress and oxidative stress signaling pathways in the heart - Jin, Jung-Kang; Sandmann, Christoph; Doroudgar, Shirin (Circulation research, 2017)
Rationale: Endoplasmic reticulum (ER) stress causes the accumulation of misfolded proteins in the ER, activating the transcription factor, ATF6 (activating transcription factor 6 alpha), which induces ER stress response genes. Myocardial ischemia induces the ER stress response; however, neither the function of this response nor whether it is mediated by ATF6 is known. Objective: Here, we examined the effects of blocking the ATF6-mediated ER stress response on ischemia/reperfusion (I/R) in cardiac myocytes and mouse hearts. Methods and Results: Knockdown of ATF6 in cardiac myocytes subjected to I/R increased reactive oxygen species and necrotic cell death, both of which were mitigated by ATF6 overexpression. Under nonstressed conditions, wild-type and ATF6 knockout mouse hearts were similar. However, compared with wild-type, ATF6 knockout hearts showed increased damage and decreased function after I/R. Mechanistically, gene array analysis showed that ATF6, which is known to induce genes encoding ER proteins that augment ER protein folding, induced numerous oxidative stress response genes not previously known to be ATF6-inducible. Many of the proteins encoded by the ATF6-induced oxidative stress genes identified here reside outside the ER, including catalase, which is known to decrease damaging reactive oxygen species in the heart. Catalase was induced by the canonical ER stressor, tunicamycin, and by I/R in cardiac myocytes from wild-type but not in cardiac myocytes from ATF6 knockout mice. ER stress response elements were identified in the catalase gene and were shown to bind ATF6 in cardiac myocytes, which increased catalase promoter activity. Overexpression of catalase, in vivo, restored ATF6 knockout mouse heart function to wild-type levels in a mouse model of I/R, as did adeno-associated virus 9–mediated ATF6 overexpression. Conclusions: ATF6 serves an important role as a previously unappreciated link between the ER stress and oxidative stress gene programs, supporting a novel mechanism by which ATF6 decreases myocardial I/R damage.